Macrophages in Acute Myeloid Leukaemia: Significant Players in Therapy Resistance and Patient Outcomes - Miari, Katerina E.; Guzman, Monica L.; Wheadon, Helen; Williams, Mark T. S. (Frontiers in Cell and Developmental Biology, 2021)
Acute Myeloid Leukaemia (AML) is a commonly occurring severe haematological malignancy, with most patients exhibiting sub-optimal clinical outcomes. Therapy resistance significantly contributes towards failure of traditional and targeted treatments, disease relapse and mortality in AML patients. The mechanisms driving therapy resistance in AML are not fully understood, and approaches to overcome therapy resistance are important for curative therapies. To date, most studies have focused on therapy resistant mechanisms inherent to leukaemic cells (e.g. TP53 mutations), overlooking to some extent, acquired mechanisms of resistance through extrinsic processes. In the bone marrow microenvironment (BMME), leukaemic cells interact with the surrounding bone resident cells, driving acquired therapy resistance in AML. Growing evidence suggests that macrophages, highly plastic immune cells present in the BMME, play a role in the pathophysiology of AML. Leukaemia-supporting macrophage subsets (CD163+CD206+) are elevated in preclinical in vivo models of AML and AML patients. However, the relationship between macrophages and therapy resistance in AML warrants further investigation. In this review, we correlate the potential links between macrophages, the development of therapy resistance, and patient outcomes in AML. We specifically focus on macrophage reprogramming by AML cells, macrophage-driven activation of anti-cell death pathways in AML cells, and the association between macrophage phenotypes and clinical outcomes in AML, including their potential prognostic value. Lastly, we discuss therapeutic targeting of macrophages, as a strategy to circumvent therapy resistance in AML, and discuss how emerging genomic and proteomic-based approaches can be utilized to address existing challenges in this research field.